The burden of symptomatic patients with chronic spontaneous urticaria: a real-world study in Korea - Young-Min Ye; Young-Il Koh; Jeong-Hee Choi; Mi-Ae Kim; Jung-Won Park; Tae-Bum Kim; Young-Hee Nam; Yoon-Seok Chang; Hae-Sim Park (The Korean Journal of Internal Medicine, 2022)
Background/Aims Chronic spontaneous urticaria (CSU) poses a considerable burden both on the quality of life (QoL) of individual patients and on healthcare systems. Real‑world data evaluating the disease burden of CSU are limited in this country. This study evaluated the disease burden and healthcare resource utilization (HRU) among symptomatic CSU patients. Methods This multicenter, noninterventional, retrospective, and cross-sectional study assessed CSU patients symptomatic for more than 6 months despite step-wise H1-antihistamine medications. Primary outcomes included Urticaria Activity Score over 7 days (UAS7) and Chronic Urticaria QoL scale (CU-QoL). Secondary outcomes included EuroQol 5-Dimension 5-Level (EQ-5D-5L), Dermatology Life Quality Index (DLQI), association of disease activity with QoL, medications used for the past 6 months, and HRU. Results Five hundred patients with CSU were enrolled. Mean disease duration was 3.7 years. Based on UAS7, 22.2% of patients were in well-controlled status and 31.2%, 28.4%, and 18.2% of them had mild, moderate, and severe disease, respectively. Mean CU-QoL and DLQI scores were 57.5 ± 29.7 and 10.2 ± 7.6, respectively, while the EQ-5D-5L utility score was 0.8 ± 0.2. H1-antihistamines were prescribed to 95% of patients, while omalizumab was prescribed to 33% of patients. Most patients (98%) had outpatient visits in the past 6 months. Negative correlations were noted between UAS7 and CU-QoL, EQ-5D-5L, EQ-5D-5L visual analog scale scores, but a positive correlation was noted with DLQI score (p < 0.001 for all). The number of outpatient department visits increased with disease activity (p = 0.001). Conclusions CSU affects QoL, leading to increased HRU, particularly in patients with severe disease.